2022
DOI: 10.1177/10556656221093292
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Source of Patient Education for Transcranial Craniosynostosis Procedures

Abstract: Introduction The internet has improved access to knowledge, with a reported 72% of internet users accessing health information online. YouTube is the most popular video-sharing website and is a frequently accessed source for health information. There are concerns, however, that patients and carers may be unable to identify and filter for trustworthy sources of information on these platforms. This study aimed to assess the quality of videos that are likely to be accessed when families search YouTube for transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Srivastav et al 30 evaluated videos on YouTube™ about feeding infants with cleft lip and palate and reported that 65.5% of included videos were classified as poor and suboptimal content. Another study showed that YouTube™ videos related to transcranial procedures for managing craniosynostosis were not sufficient for transferring high‐quality information to families 31 . In the present study, according to content scores, 34% of included videos were classified as low‐content, 60.6% were classified as moderate‐content, and only 5.3% were classified as high‐content.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Srivastav et al 30 evaluated videos on YouTube™ about feeding infants with cleft lip and palate and reported that 65.5% of included videos were classified as poor and suboptimal content. Another study showed that YouTube™ videos related to transcranial procedures for managing craniosynostosis were not sufficient for transferring high‐quality information to families 31 . In the present study, according to content scores, 34% of included videos were classified as low‐content, 60.6% were classified as moderate‐content, and only 5.3% were classified as high‐content.…”
Section: Discussioncontrasting
confidence: 47%
“…27 Despite the beneficial effect of accurate information covering the decision-making process and psychological needs of Several studies evaluated YouTube™ as a source of information on craniofacial conditions for either patients or healthcare professionals. 26,29,30,31 were not sufficient for transferring high-quality information to families. 31 In the present study, according to content scores, 34% of included videos were classified as low-content, 60.6% were classified as moderate-content, and only 5.3% were classified as high-content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations